2022
DOI: 10.1088/1755-1315/1111/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Permanent Magnet Structure on The Performance of LSPMSM with a Power of 22 kW and 3000 rpm

Abstract: Energy efficiency and sustainability are important goals for countries all over the world. With the advancement of material technology, many new generations of high-efficiency motors are being researched and developed to replace induction motors (IM) to save energy. Line-start permanent-magnet synchronous motors (LSPMSM) are high-performance and ultra-high-performance motors that are emerging as an alternative to squirrel-rotor induction motors. Constructing the permanent magnets in the rotor is critically imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the complexity and influ ence of the rotor structure in the LSPMSM 3,000 rpm. The paper [13] analyzes the performance of the 2pole LSPMSM with a rotor structure with three magnets, the magnets are separated by magnetic steel bridges of the rotor. The research results show that with the proposed magnet structure, the mo tor can achieve IE2 efficiency.…”
Section: Electrical Complexes and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the complexity and influ ence of the rotor structure in the LSPMSM 3,000 rpm. The paper [13] analyzes the performance of the 2pole LSPMSM with a rotor structure with three magnets, the magnets are separated by magnetic steel bridges of the rotor. The research results show that with the proposed magnet structure, the mo tor can achieve IE2 efficiency.…”
Section: Electrical Complexes and Systemsmentioning
confidence: 99%
“…This will be very beneficial to the designers and operators of the magnetic sorting machine when they are modifying the electromagnetic structure's param eters in order to optimize the distribution of magnetic fields in space and raise the machine's operational efficiency. The four fundamental steps of the FEM method are as follows [13]:…”
Section: Fig 3 Rotor Configuration Of the Proposed Lspmsmmentioning
confidence: 99%
“…The LSPMSM model's performance can be improved by using computer-aided design optimization procedures [12][13][14]. LSPMSMs are of great interest to researchers because of their high energy efficiency due to the growing interest of manufacturers in energy-efficient units [8][9][10][11]. The LSPMSM model's performance can be improved by using computer-aided design optimization procedures [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to [3], the efficiency levels from IE1 to IE5 of the motor depend on its power and have a dependency graph, as shown in Figure 1. The rapid development of Neodymium (NdFeB) rare earth permanent magnet technology with high magnetic field density and large energy product has spurred the development of high-efficiency motors, including line start permanent magnet synchronous motor (LSPMSM) [4,5]. LSPMSM is a hybrid between induction and synchronous motors by placing permanent magnets in the rotor of induction motors.…”
mentioning
confidence: 99%